Pengaruh Financial Technology Terhadap Profitabilitas Bank Mandiri - Nurul Azmi; Yuni Yuniawati (Journal of Trends Economics and Accounting Research, 2022)
The purpose of this study was to determine the effect of financial technology on Bank Mandiri's profitability before and during the Covid 19 pandemic. The analytical method in this study uses secondary data, namely data obtained from the annual financial reports contained on the official website www.bankmandiri.co.id and perform a different test using SPSS. The results showed that the effect of financial technology on Bank Mandiri's profitability before and during the Covid 19 pandemic was no difference in the use of financial technology with the variables ROA, ROE, and NIM, on Bank Mandiri's profitability for the 2018-2021 period.